LGBT Deviations in School-Age Children (Literature Review) - Putra, Juniawan Mandala; M, Erlina Puspitaloka; Zairil, Zairil (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
The phenomenon of LGBT among school-aged children in Indonesia has become increasingly prominent, driven by growing access to social media and declining value control within educational and family environments. This study employs a qualitative descriptive approach using literature review to examine the causes, forms of deviation, and societal responses to LGBT-related behaviours in school settings. The findings indicate that such deviations are influenced by various factors, including psychological imbalance, peer influence, weak parental supervision, and the widespread availability of digital content that normalises non-binary gender expression. The issue is further exacerbated by the lack of preventive education in schools, with 43.5% of institutions reportedly having no dedicated programmes to address LGBT awareness. Therefore, a collaborative effort involving schools, families, and the wider community is essential to instil value-based awareness, promote character education, and strengthen digital literacy as a means of early prevention of sexual behaviour deviation.